2015
DOI: 10.2131/jts.40.235
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Brazilian propolis exerts estrogenic effect in ovariectomized rats

Abstract: -Propolis, a natural product derived from plants by honeybees, is a mixture of several hundred chemicals, including flavonoids, coumaric acids, and caffeic acids, some of which show estrogen-like activity. In this study, the estrogenic activity of crude ethanolic extract of Brazilian propolis was determined using several in vitro and in vivo assays. Propolis was found to bind to human estrogen receptors (ERs). Furthermore, propolis induced the expression of estrogen-responsive genes in ERpositive MCF-7 and Ish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Our hypothesis is that the neonatal chronic stress induces the apoptosis of granulosa cells and may reduce 17-beta estradiol biosynthesis, and consequently reduce the quality of the ovum. Our results are in agreement with the findings reported by Okamoto et al , showed that oral administration of propolis induces estrogenic activity in estrogen target organs in vivo suggesting that propolis is a useful dietary source of phytoestrogens and a promising treatment for post-menopausal symptoms ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our hypothesis is that the neonatal chronic stress induces the apoptosis of granulosa cells and may reduce 17-beta estradiol biosynthesis, and consequently reduce the quality of the ovum. Our results are in agreement with the findings reported by Okamoto et al , showed that oral administration of propolis induces estrogenic activity in estrogen target organs in vivo suggesting that propolis is a useful dietary source of phytoestrogens and a promising treatment for post-menopausal symptoms ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…The several reports have shown that the ovaries of the female rats contain only the oocytes immediately after birth and are without any follicles, and this means that follicular development and evolution process occurs after the birth in the rats ( 29 , 33 ). As well, it is known that primordial follicles are created three days after the birth and lead to the formation of primary follicles immediately after their growth and differentiation process ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical composition of propolis greatly varies according to the plants that can be found in a specific region [18, 19]. The caffeic acid derivatives has been detected as potential estrogenic components in Cameroonian and Korean propolis, while Okamoto et al [42] attributed the estrogenic effects of Brazilian propolis to the well-known phytoestrogens Kaempferol, quercetin, naringenin, Biochanin A and formononetin. These aforesaid suggest a regional difference in estrogenic components of propolis.…”
Section: Discussionmentioning
confidence: 99%
“…There was a non-significant increase of uterine tumors incidence in high dose female group, and we concluded that in the present conditions, 2.5% EEP is likely to exert estrogenic activity but lacks the carcinogenicity in the uterus of Wistar Hannover rats. Previously, the estrogenic effects of propolis were demonstrated through the activation of an estrogen receptor [ 26 ]. For instance, EEP was found to bind human estrogen receptors and to induce the expression of estrogen-responsive genes in ER-positive MCF-7 and Ishikawa cells and to induce estrogenic activity in ER-expressing organs of ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ethanol-extracted Brazilian green propolis (EEP) exerted promoting effect on F344 rat bladder carcinogenesis initiated with N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN) [ 23 ]. Moreover, it was recently found to exert estrogenic effect in ovariectomized rats, significantly increasing uterine luminal epithelium thickness and ductal cell proliferation in the mammary glands [ 26 ]. Therefore, there is a doubt concerning propolis carcinogenicity in the liver, bladder, mammary gland and uterus.…”
Section: Introductionmentioning
confidence: 99%